Atuação do enfermeiro na manutenção do cateter central de inserção periférica (PICC) em neonatologia: uma revisão de literatura - SILVA, Camila Ferreira da (2019)
The Peripherally Inserted Central Catheter (PICC) has been widely used in neonatal intensive care units for venous access in the medium and long term, being the first choice for central access after umbilical catheterization. This study aims to analyze the recommendations available in the database for the maintenance and the main causes of catheter loss in Neonates. This is a literature review. The search for the study was carried out from papers indexed in the database BDENF, LILACS, SciELO, books published on the subject, a thesis and three dissertations between the years 2001-2012. Used as descriptors for the following terms: Newborn, catheterization peripheral, Nursing. The assessment of the PICC should be performed daily and up to the professional nursing surveillance continues to detect changes related bloodstream infection. We conclude that it is essential that nurses are trained and prepared technical and scientifically identify all possible complications arising from the use of PICC.